Effect of coiled-coil peptides on the function of the type III secretion system-dependent activity of enterohemorragic Escherichia coli O157:H7 and Citrobacter rodentium - Larzabal, Mariano (2013)
Many animal and human pathogenic Gram-negative bacteria such as Salmonella, Yersinia, enterohemorrhagic Escherichia coli (EHEC), and enteropathogenic Escherichia coli (EPEC) possess a type III secretion system (TTSS) that is used to deliver virulence proteins directly into the host cell. Recent evidence has suggested that CoilA and CoilB, two synthetic peptides corresponding to coiled-coil domains of the translocator protein EspA, are effective in inhibiting the action of TTSS from EPEC. In the current study, the action of these coiled-coil peptides on the TTSS of EHEC O157:H7 and Citrobacter rodentium was examined. CoilA and CoilB showed to be effective in reducing the red blood cell lysis mediated by EHEC O157:H7 and the in vitro secretion of translocator proteins EspB and EspD by EHEC O157:H7 and EspD by C. rodentium. Treatment of mice with CoilA and CoilB peptides prevented colon damage when the animals were inoculated with C. rodentium. Colon samples of the non-treated group showed areas with loss of superficial epithelium, damaged cells, and endoluminal mononuclear inflammatory infiltrate, consistent with histological lesions induced by C. rodentium, whereas mice treated with the synthetic peptides displayed normal surface epithelium showing a similar structure as the uninfected control group. These encouraging results prompt us to test coiled-coil peptides as treatment or vaccines in other models of bacterial infections in future work.